The reptiles of Bungo Range - Indraneil, Das; Izneil, Nashriq; Pui, Yong Min (UNIMAS Publisher, 2023)
The proposed Bungo Range National Park, in the Kuching Division of Sarawak, encompasses a total area of 8,095 ha, and comprises a rolling landscape of sandstone ridges and lowland rainforests, hemmed in by tower karst and at present, villages and agricultural land. The range of habitat types encompassed, including the presence of wetlands and several substrate types make the area of potential importance for herpetofaunas.